Case Report of Myeloid Sarcoma Masquerading as In-Transit Metastasis at a Previous Melanoma Site: Avoiding a Diagnostic Pitfall. (November 2018) - Curry, Jonathan L.; Tetzlaff, Michael T.; Wang, Sa A.; Landon, Gene; Alouch, Nail; Patel, Sapna P.; Nagarajan, Priyadharsini; Gupta, Shiva; Aung, Phyu P.; Devine, Catherine E.; Khoury, Joseph D.; Loghavi, Sanam; et al.
Abstract : Abstract: Myeloid sarcoma is a rare extramedullary hematologic malignancy. Accurate and timely diagnosis may be challenging because myeloid sarcoma is known to mimic solid tumors, including hepatobiliary, nasopharyngeal, and breast carcinomas. We report a case of myeloid sarcoma that developed in the primary tumor lymphatic drainage field of a previously treated intermediate-thickness cutaneous melanoma, clinically and radiographically mimicking an in-transit metastasis, in a patient with myelodysplastic syndrome. The diagnosis of myeloid sarcoma was achieved after surgical excision of the mass and pathological examination that included extensive immunohistochemical studies. Awareness of such an unusual clinical presentation can help reduce diagnostic delay and ensure that adequate tissue is obtained for pathological examination and ancillary studies that are critical for accurate diagnosis and appropriate patient management.